The ubiquitin-like modifier FAT10 is not essential for MHC-I antigen presentation - Pach, Natalie; Ochs, Sarah; Cao, Jinjing; Ottlinger, Julia; Aichem, Annette; Basler, Michael (Frontiers in Immunology, 2025)
IntroductionThe presentation of pathogen-derived antigens on major histocompatibility complex (MHC) class I is crucial for the antiviral immune response. Degradation of intracellular pathogen-derived proteins by the 26S proteasome generates peptides that can be loaded on MHC-I molecules and presented to cytotoxic T cells. The cytokine-inducible ubiquitin-like modifier (ULM) HLA-F adjacent transcript 10 (FAT10) is encoded in the MHC locus and targets its substrates for proteasomal degradation. Therefore, it acts as an alternative signal for protein degradation, indicating a role in generating the peptide pool for MHC-I presentation. In this study, we aimed to elucidate the role of FAT10 in MHC class I presentation. MethodsUsing different human and mouse cell lines deficient for FAT10, the effect of FAT10 on MHC-I surface expression and recovery was studied. For the evaluation of antigen presentation of viral and endogenous epitopes, T cell hybridoma assays and flow cytometry analysis were used.ResultsIn our study, using model antigens and FAT10-deficient cells, we found that the absence of FAT10 does not affect the abundance of MHC-I molecules or the generation of endogenous and virus-derived MHC-I epitopes. Furthermore, we demonstrated that the cytotoxic T cell response to different viruses remains unchanged in FAT10-deficient mice compared to wild-type mice.DiscussionIn summary, our findings indicate that the lack of FAT10 does not impact antigen presentation or the cytotoxic T-cell response across a number of different MHC-I-restricted peptides. Hence, we conclude that the contribution of FAT10 to MHC-I antigen presentation has previously been overestimated.